Gambaran Implementasi Alur Prosedur Pelayanan & Penyelenggaraan Rekam Medis di RS Muhammadiyah Selogiri, Wonogiri - Arifatun Nisaa Nisaa (APIKES Bhumi Husada Jakarta, 2021)
Background : Medical records are managed based on a standard structure, provided that the implementation system is evaluated to produce information and has a confidentiality standard that must be maintained. The medical record document is in principle stored properly in the hospital so that it is easy to retrieve every service information need for patients. Objective : To find out how the implementation of service procedures and management functions as well as the implementation of medical records at the Selogiri Muhammadiyan Hospital. Methods : The type of research used in this study is descriptive with a qualitative approach. While the research design used is phenomenology. Results : The management system of medical record data at Muhammadiyah Selogiri Hospital which includes assembling, coding and indexing, analizing and reporting, filing. The medical record system in the Wonogiri Selogiri Muhammadiyah Hospital includes: The Naming System uses the patient's own name in accordance with valid identification such as KTP, birth certificate, SIM, etc. The numbering system uses the Unit Numbering System (UNS). The system uses the Digit Filing (TDF) and Straight Numerical Filing (SNF) terminals. Conclusion : It is necessary to incorporate the SNF alignment system into the TDF alignment system as a whole to facilitate and accelerate the retrieval of medical record documents. Filling officers need to increase accuracy in storing medical record documents so that missfile does not occur frequently. Keywords : Procedure Flow, Procedure of Service and Management Functions, Medical Record Implementation